2019
DOI: 10.1002/jbm.a.36839
|View full text |Cite
|
Sign up to set email alerts
|

The characteristic regulation of gene expression Lbp and Sod3 in peri‐implant connective tissue of rats

Abstract: The aim of this study was to investigate the characteristic gene expression profile and localization of peri-implant connective tissue (PICT) compared with those of periodontal connective tissue (PCT) and oral mucosal connective tissue (OMCT). Upper first molar of 5-week-old rats were extracted and titanium implant were placed for PICT group. PCT and OMCT were used as control. Laser microdissected connective tissue at 4 weeks used for microarray analysis. The expression and localization of selected genes were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…Previous animal studies have reported that OTM increased ROS-mediated oxidative stress in rat periodontal tissues (71), and rats with high gingival oxidative stress levels have lower SOD3 expression in gingival tissues with increased alveolar bone resorption (57). Increased ROS and decreased SOD3 expression in rat peri-implant connective tissues have also been observed following dental implant placement (72). Furthermore, excessive ROS in osteoblasts suppresses cell viability, SOD3 expression, and bone formation-related genes (56).…”
Section: Chapter V Discussionmentioning
confidence: 99%
“…Previous animal studies have reported that OTM increased ROS-mediated oxidative stress in rat periodontal tissues (71), and rats with high gingival oxidative stress levels have lower SOD3 expression in gingival tissues with increased alveolar bone resorption (57). Increased ROS and decreased SOD3 expression in rat peri-implant connective tissues have also been observed following dental implant placement (72). Furthermore, excessive ROS in osteoblasts suppresses cell viability, SOD3 expression, and bone formation-related genes (56).…”
Section: Chapter V Discussionmentioning
confidence: 99%